KOMUNIKASI INTERPERSONAL KARYAWAN PURCHASING DENGANFOOD AND BEVERAGE DIVISION HOTEL BASKO PADANG - DWITAMA, FRISCA SASRI; Yuliana, Yuliana; Suyuthie, Hijriyantomi (Journal of Home Economics and Tourism, 2016)
This research aimed to describe the employee interpersonal communication with employees purchasing food and beverage division which in terms of openness, confidence, verbal and nonverbal communication, empathy, positivity, and conflicts in interpersonal relationships. This type of research is descriptive qualitative data. Techniques of collecting data using interviews, observation, and documentation. From the results of this study concluded that the openness indicator is only a fraction of employees are open in communicating about the interpersonal realize yourself, accept yourself, the desire to respond honestly and desire to convey information. In the case of most of the employees have confidence build confidence and mutual trust. Verbal and nonverbal communication only some employees are to communicate effectively and listen while understanding. Most employees have empathy in terms of feel the problems of others. Most give positive attention and gives a feeling of positive and most participated in solving the problem if there is a conflict. Keywords: InterpersonalCommunication, Hotel, Purchasing, Food andbeveragedivision